My brother is a superhero - Solomons, David (New York, N.Y. : Nosycrow, 2015)
Eleven-year-old Luke, a hardcore fan of comics and superheroes, is jealous when his undeserving older brother Zack is zapped by an alien and turned into a superhero, until a plot to destroy the Earth incapacitates Zack, and Luke, accompanied by Lara, the nosey girl next door, must come to the rescue.
Bulletin (Center for Children's books)
Publisher's Weekly
School Library Journal starred
Bulletin (Center for Children's books), September 2015
Kirkus Review, May 2015
Publisher's Weekly, May 2015
Keywords: Brothers -- Juvenile fiction; Comic books, strips, etc. -- Juvenile fiction; Superheroes -- Juvenile fiction; Brothers -- Fiction; Cartoons and comics -- Fiction; Superheroes -- Fiction; Brothers -- Fiction; Comic books, strips, etc. -- Fiction; Superheroes -- Fiction